Pengaruh Reward, Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT. PLN (Persero) ULP Sampit - Samalla, Vieda; Nasir, Moechammad (Jurnal EMT KITA, 2024)
Employee performance at PT PLN (Persero) ULP Sampit is influenced by three main factors, namely organizational culture, leadership style, and rewards. Analysis was carried out through a series of instrument tests, classical tests and hypothesis tests in surveys involving respondents using questionnaires. The collected data was analyzed using SPSS version 24 statistical software. The results showed that (1) rewards have an impact on employee performance, although not significant; (2) leadership style also has an impact on employee performance, but not significantly; and (3) organizational culture has a significant and positive influence on employee performance.